ANALISIS KEBUTUHAN TENAGA KERJA BAGIAN PELAPORAN RUMAH SAKIT MENGGUNAKAN METODE ANALISIS BEBAN KERJA KESEHATAN (ABK KES) - Hesty Latifa Noor; Siti Nur Qomariyah; Sri Wahyuningsih Nugraheni (Universitas Duta Bangsa Surakarta, 2023)
ABK Kes is a method of calculating the need for health human resources based on the workload carried out by each type of health human resource according to their main tasks and functions. There is a double job, the amount of data that needs to be processed results in reports that cannot be reported properly, on time and officers cannot carry out work in accordance with the description of their main tasks and functions. The purpose of this study was to determine the needs of the workforce with the health workload analysis method (ABK Kes) in the medical record unit reporting section at Muhammadiyah Lamongan Hospital.The subjects in this study were reporting officers. While the object in this study is the workload of reporting officers. Data collection methods are by interview and observation. Data processing is done by collecting, editing, tabulating and presenting data in a qualitative descriptive form. The results of this study are health facilities of the general hospital type and the type of health human resources reporting section, the available WKT is 1240 hours/year and 74400 minutes/year, the workload standard is 538,800, the FTP value is 1.91% and the STP value is 1.13%, and the results of the calculation of the labor requirements for the reporting section of the ABK Kes method were 6 people. The conclusion of this study is that the reporting section's need for health human resources is 6 health human resources currently only 3 health human resources are available. The author suggests that it is better to add 3 health human resources.